The role of lateral and medial posterior tibial slope in anterior cruciate ligament injuries: a case-control study - Chacko, Ankith; T. C., Ranjith; Babu, Murukan; Toms, Ajith; John, Susan (International Journal of Research in Orthopaedics, 2022)
Background: The anterior cruciate ligament (ACL) is one of the major stabilisers of the knee and is the most frequently involved ligament in knee injuries and related functional instability. The objective of the study was to compare the lateral posterior tibial slope (LPTS) and medial posterior tibial slope (MPTS) among those with ACL injury and those with the intact ligament. Methods: MRI of 65 (male-43, female-22) ACL injured and 65 (male-58, female-7) ACL intact knees were studied. Using RadiAnt DICOM viewer software, the slopes of both medial and LPTS s were measured. The statistical analysis was performed by IBM SPSS 25. Associations between various factors were assessed using the Chi square test for categorical variables and independent t test were done for quantitative variables. P<0.05 had been considered statistically significant. Results: Among cases the mean LPTS was 10.230±3.930 and mean MPTS was 6.610±3.490. Among controls, mean LPTS was 8.460±3.630, mean MPTS was 5.510±2.910. Case had a statistically significant (p=0.009) steeper LPTS than control population. MPTS of cases were steeper than the control population with no statistical significance (p=0.055). Conclusions: In this study, the LPTS was significantly increased among patients with ACL injury as compared with ligament-intact controls. LPTS measurements should be considered as a significant independent modifiable risk factor for ACL injury.